Como pode o movimento ser um ato? - Barbosa, Rafael Mello (Laboratório OUSIA, 2019)
The general objective of this article is to show that distinct notions of movement imply in different understandings of world and knowledge and vice versa. The specific objective is to present the notion of movement elaborated in the Physics of Aristotle and its reception from Simplícius.